Karakter Arthur Fleck Dalam Kritik Sosial Film Joker (2019) - Rahman Hakim; Riesta Ayu Oktarina; Edelweis Putri Prima (DIGICOM : Jurnal Komunikasi dan Media, 2023)
For Fleck Arthur's character in the thematic film entitled Joker in 2019, the aim is to find out whether social criticism (in relation to actions, tactics, and design) Lebenswelt communication concepts) rests on how reality, depictions and teachings have eroded. . played by the character Flake in the 2019 Joker film. This study used a qualitative research method, the constructivism model. In this qualitative research, data collection techniques used the documentation method, namely recording directly the scenes from the film. This research was conducted based on a scene-by-scene analysis of the role of Arthur Fleck's character in the Joker film, which can be categorized according to Habermas' social criticism ideas, namely communicative action thinking, strategic combat action and ideas from Lebenswelt, namely world life. This classification requires a process of understanding the semiotic model of John Fiske, studies at the realist, representational, and ideological levels. The output for this research is the legitimacy of causal responses from Joker's communicative actions, namely skepticism, radicalism, anarchy to cynicism. Arthur's strategic efforts spark resistance and commotion; and Arthur Flack's Lebenswelt components were eliminated, creating a superior hierarchy.